Intensitas dan Prevalensi Parasit Pada Insang Ikan Nila yang dibudidayakan di Balai Benih Ikan (BBI) Sentral Sangeh - Purnama Sari, I Gusti Ayu Agung; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga; Suryaningtyas, Endang Wulandari (Current Trends in Aquatic Science; Vol 6 No 2 (2023), 2023)
Parasites in the body of cultivated fish will cause harm to the fish, because the parasites take nutrients from their hosts, it is necessary to study the intensity and prevalence of parasites in tilapia ( Oreochomis niloticus ) in order to determine the density of parasite attacks and the percentage of parasites in tilapia. Samples of tilapia ( Oreochomis niloticus ) were taken from the Central Sangeh Fish Seed Center (BBI). The research was conducted for 3 months from October 4 th 2022 to December 13 2022 randomly sampling. Samples of tilapia ( Oreochomis niloticus ) examined were 36 samples of Nila Nirwana fish. The parasites found in the external organs (ectoparasites) were only found in the tilapia gills, while for the internal organs (endoparasites) parasites were not found in both the stomach and intestines of the fish. The ectoparasites found were Dactylogyrus sp. (2181 ind) and Gyrodactylus sp. (157 ind). The highest intensity was in the genus Dactylogyrus of 60.6 ind/fish including the severe category, while for the genus Gyrodactylus of 4.4 ind/head including the low category. The highest prevalence value was in the genus Dactylogyrus with 92% in the always category while in the genus Gyrodactylus it was 78% in the usual category. This study’s supporting data for water quality includes temperature, pH, DO, and ammonia. Where temperature during the study ranged from 28-30 o C, pH or acidity ranged from 7.6-8.5, and DO or dissolved oxygen ranged from 7.3-8.4 mg/L. The water quality result in this study were normal for fish farming.